Exploring Analogical Reasoning through Iconicity in Sign Language and Gestures - (:unkn) unknown (My University, 2026)
The team at Pontificia Universidad Católica Del Peru led by Dr. Rodríguez Mondoñedo will review and explore reported iconicity criteria in Peruvian Sign Language (LSP) and American Sign Language (ASL) and works on other sign languages and non-verbal commu